Modeling and visual syntax: an essential connection for training of project thinking (Revista de Ensino em Artes, Moda e Design, 2020)
The higher education in fashion design must be able to promote skills that allow the student to connect variables and concepts in the search for coherent solutions throughout the design process. Therefore, this paper aims to discuss a didactic action called Projeto Integrador, promoted by the Fashion Design Course at Universidade Estadual de Londrina, which operates according to a pedagogical project based on ProjectBased Learning (PjBL) and the interdisciplinary approach. Presents the didactic efforts made to promote the development of the skills involved in the visual syntax of the fashion garments and the fundamental concepts of modeling throughout the de- sign process. The results achieved were positive for the educational context, promo- ting theorical and practical connections and the students’ immersion in the process of synthesis of syntactic principles and formal experimentation.
Keywords: desing teaching; modeling; visual syntax